Evaluation of the embolic effect and degradability of gelatin microspheres and gelpart particles. Issue 3 (June 2013) - Nitta, Norihisa; Ohta, Shinichi; Sonoda, Akinaga; Watanabe, Shobu; Otani, Hideji; Tomozawa, Yuki; Nitta-Seko, Ayumi; Tsuchiya, Keiko; Mukaisho, Kenichi; Takahashi, Masashi; Murata, Kiyoshi; Tabata, Yasuhiko
Abstract Purpose: To evaluate the embolic effect and degradability of gelatin microspheres (GMS) and Gelpart particles (GPS) in dogs subjected to hepatic embolization. Material and methods: We subjected 20 beagles to embolization of the hepatic artery (HA) and assessed the embolic effects of GMS measuring 500 μm in dry and 1 mm in wet state and of 1-mm GPS, porous gelatin embolic particles. We obtained celiac angiographs before and immediately after embolization and two, 14, and 28 days later; the livers were histopathologically evaluated. Reperfusion of HA was assessed by inspecting the arterial branches. We checked the liver specimens for residual GMS, injury to surrounding tissues, and inflammatory changes, and investigated embolic formation in the HA. Results: The mean amount of injected GMS and GPS was 15.5 and 14.5 mg, respectively. While none of the dogs manifested HA reperfusion two days post-embolization, there was angiographic evidence of complete reperfusion 28 days after embolization. In all dogs, histopathological study showed arterial inflammatory changes and injury of surrounding tissues irrespective of the embolization materials used. These findings were pronounced on day 28 in dogs injected with GMS. Conclusion: There was no difference in the embolic effects of GMS and GPS nor in their degradability in dogs subjected to hepatic embolization.